Impact of legal institutions on IPO survival: A global perspective - Espenlaub, Susanne; Goyal, Abhinav; Mohamed, Abdulkadir (Journal of Financial Stability, 2016)
Around the world, investors, practitioners, regulators and policy makers seek to understand whether, when and why recently listed stocks, initial public offerings (IPOs) are delisted rather than continue trading (survive). Using data on 7,627 IPOs issued during 2000–2008 across 32 countries, we explore the impact of the legal system on IPO survival. We find that IPOs in countries with better investor protections remain listed for longer. This suggests that better legal systems increase the net benefits companies derive from staying listed. We also provide evidence that better legal systems increase the effectiveness of IPO certification by venture capitalists, underwriters and auditors.